2010 IEEE Symposium on Security and Privacy 2010
DOI: 10.1109/sp.2010.19
|View full text |Cite
|
Sign up to set email alerts
|

Tamper Evident Microprocessors

Abstract: Abstract-Most security mechanisms proposed to date unquestioningly place trust in microprocessor hardware. This trust, however, is misplaced and dangerous because microprocessors are vulnerable to insider attacks that can catastrophically compromise security, integrity and privacy of computer systems. In this paper, we describe several methods to strengthen the fundamental assumption about trust in microprocessors. By employing practical, lightweight attack detectors within a microprocessor, we show that it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…There have been some recent research efforts to achieve the above objectives via design obfuscation and/or isolation [19][20][21][22]. These solutions facilitate to mitigate some HT threats, but the associated design cost is quite high and there is no guarantee that ICs would be HT-free with these design methodologies.…”
Section: Hardware Trust Challengesmentioning
confidence: 99%
“…There have been some recent research efforts to achieve the above objectives via design obfuscation and/or isolation [19][20][21][22]. These solutions facilitate to mitigate some HT threats, but the associated design cost is quite high and there is no guarantee that ICs would be HT-free with these design methodologies.…”
Section: Hardware Trust Challengesmentioning
confidence: 99%
“…Waksman and Sethumadhavan previously observed that there are finitely many types of deterministic, digital backdoor triggers that can be injected by an inside designer [26]. We leverage this observation and devise methods to disable all of these types of triggers by obfuscating or scrambling inputs supplied to the hardware units in order to prevent those units from recognizing triggers.…”
Section: However Even If We Cannot Find the Malicious Logic We Claimentioning
confidence: 99%
“…Waksman and Sethumadhavan proposed a different method that detects unusual hardware behavior at runtime using a self-monitoring on-chip network [26]. This method, like the previous one, focusses on detection (as opposed to prevention).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Censorship at storage level consists in performing a selective filtering on the content of a peer and aims at blocking the resource as soon as its presence is detected. To avoid this type of attack, techniques such as replication of resources [5,11] and encryption of file chunks [19,30] have been proposed.…”
Section: Related Workmentioning
confidence: 99%